Narrative self-recreation in virtual reality - Georgieva, Iva; Georgiev, Georgi V. (Frontiers in Virtual Reality, 2022)
The narrative essence of human nature is that humans are storytellers, and this ability helps to constitute their identities. The challenges that can disrupt this innate ability are adverse events that affect human perception of the world and undermine the meaning one finds in reality. Such events might range from short-term stressors to long-term testing conditions, such as pandemics. The tools to overcome these negative effects and achieve self-preservation might be sought in individual storytelling abilities in relation to self-constitution and identification. An example of an interactive digital narrative medium that provides a platform for such expression of complex issues is Virtual Reality, which has been used as a visual narrative storytelling tool for decades. This research begins with the notion of trauma, as seen in a new light—as a break in the individual story that is used to explain one’s life and the story that needs to be intertwined and re-adapted to one’s overall lifetime. In the healthcare context, this experience can be most effectively presented in Virtual Reality because it offers added meaning, potential choices, closure, and resolution as a method of utilization. Therefore, Virtual Reality can be seen not only as a medium whereby traumatic events can be processed, but also as an alternative viewpoint of the goal of self-(re)creation. This research discusses a theoretical proposal for ways to play with self-construction mechanisms in the context of an immersive Virtual Reality environment, to create more opportunities to change one’s narrative and, hence, one’s real-life story.